The Librarian’s Role in the Procurement of IPDN Electronic Library Materials During the Covid-19 Pandemic - Kiswanto, Kiswanto; Istiningsih, Istiningsih; Umanah, Umanah (Department Library of Governance Institut of Home Affairs, 2022)
Abstract Background: Electronic library materials are more effective and efficient than printed books. Therefore, they are popular with millennials, especially when library services are only open online during the Covid-19 pandemic and the new normal era. Librarians are required to maximize e-resources services when the budget is fully refocused on handling the Covid-19 outbreak. Purpose: This research aims to analyze the librarian’s role in procuring electronic library materials during the Covid-19 pandemic. Method: The method used is qualitative with a descriptive analysis design. Results: The results show that librarians act as administrators in selecting and procuring electronic library materials through the digital library applications “Digilib Praja” and “Smartlib IPDN.” In the policy dimension, they serve as an advisory board to the head of the library in making policies, selecting information technology-based service tools, and implementing digital book fundraising policies. In the Service Object Achievement dimension, librarians play a role in gathering information needs and ensuring electronic book purchases are based on guidelines for the IPDN Library. Conclusion: In conclusion, the role of librarians in procuring electronic library materials was sufficiently performed. They can procure IPDN e-resources through a digital book fundraising policy, which can be applied to another university as a form of innovation. Keywords: Librarian Role; Procurement of Electronic Library Materials; E-Resources; Fundraising